HUBUNGAN SIFAT FISIK DAN KIMIA TANAH DENGAN PERTUMBUHAN MERANTI MERAH DI KHDTK HAURBENTES - Exze Erizilina; Prijanto Pamoengkas; Darwo Darwo (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Failure in degraded forest rehabilitation was caused by using chosen species without pay attantion on site characterictics. Species selection by looking at site limiting factor, will increase success in degraded forest rehabilitation. This research aims to study the influence of physical and chemical soil properties on growth of Shorea leprosula Miq, Shorea palembanica Miq, dan Shorea mecisopteryx. Data was analyzed using multiple linear regression analysis with mean annual increment (MAI) of height and diameter as dependent variable and soil properties as independent variable. The results showed that growth increment of S.palembanica was the most species that influnced by soil perperties with R2 adjusted value for MAI-diameter and MAI-height repectively, 0.946 and 0.674 whereas others two Shorea have R2 adjusted value < 0.5. The research also showed that available P content was the limiting factor of the three species. There was a difference of each species in respond to the available P content. MAI-height on S. mecisopteryx and MAI-diameter and MAI-height on S. pelambanica will increase in line with decreasing available P content while S. leprosula required P available increasing in order to increase of MAI-diameter. This indicates that each species have specific response on certain soil properties content.